2005
DOI: 10.4161/cbt.4.7.1896
|View full text |Cite
|
Sign up to set email alerts
|

Small interfering RNA-induced CHFR silencing sensitizes oral squamous cell cancer cells to microtubule inhibitors

Abstract: Alterations in the function of cell cycle checkpoints are frequently detected in oral squamous cell carcinomas (OSCCs), and are often associated with the sensitivity of the cancer cells to chemotherapeutic drugs. Recently, a mitotic checkpoint gene, Chfr, was shown to be inactivated by promoter methylation and point mutations in various human tumors. Here we show that the absence of its product, CHFR, is associated with mitotic checkpoint dysfunction, and that cancer cells lacking CHFR are sensitive to microtu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
36
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 24 publications
(40 reference statements)
6
36
1
Order By: Relevance
“…Therefore, CHFR has been hypothesized to be a tumor suppressor with a potential role as a biomarker for chemotherapeutic response to Taxol (4,5). Many reports have noted that cancer cells that have lost CHFR expression are more likely to undergo apoptosis in response to microtubule poisons, which strongly supports this hypothesis (1,(5)(6)(7). The molecular mechanism by which CHFR initiates a cell cycle arrest is debated, although evidence implicates the p38/mitogen-activated protein kinase pathway, an Aurora A interaction, and/or through regulation of PLK-1 (8)(9)(10)(11).…”
Section: Introductionsupporting
confidence: 50%
“…Therefore, CHFR has been hypothesized to be a tumor suppressor with a potential role as a biomarker for chemotherapeutic response to Taxol (4,5). Many reports have noted that cancer cells that have lost CHFR expression are more likely to undergo apoptosis in response to microtubule poisons, which strongly supports this hypothesis (1,(5)(6)(7). The molecular mechanism by which CHFR initiates a cell cycle arrest is debated, although evidence implicates the p38/mitogen-activated protein kinase pathway, an Aurora A interaction, and/or through regulation of PLK-1 (8)(9)(10)(11).…”
Section: Introductionsupporting
confidence: 50%
“…A previous study has also reported that sensitivity to CDDP in endometrial cancer cells with CHFR methylation was unaltered after demethylation, whereas sensitivity to PTX decreased after demethylation, 19 while another study found no correlation between CHFR methylation and sensitivity to CDDP or VP-16 through experiments with cancer cell lines. 20 We also showed that CHFR methylation status did not affect sensitivity to other anticancer agents such as CDDP, CBDCA, GEM, VNR, CPT-11 or VP-16 (Fig. 3).…”
Section: Discussionmentioning
confidence: 83%
“…This eventually results in cell-cycle arrest and a less invasive phenotype (58). In addition to a potential role for CHFR as prognostic biomarker, CHFR promoter methylation has been proposed as biomarker for response to microtubule inhibitor taxanes in endometrial (59), cervical (59), oral (60), and gastric cancer (61). Although taxanes are not implemented in CRC treatment because they failed to demonstrate a significant clinical benefit in phase II trials (62), CRCs with CHFR promoter methylation might benefit from taxanes.…”
Section: Discussionmentioning
confidence: 99%